ENERAPAN STANDAR AUDITING DAN STANDAR PENGENDALIAN MUTU PADA KAP ANGGOTA FAPM INDONESIA - Sukrisno Agoes (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2003)
The need of the user of financial report on the financial information that is free from information risk, can only be fulfilled through auditing of the financial report, by the independent public accountant. In the level of either national or intemational show the other ways around. The national level, the result of peer review on auditors' working papers 38 Freezing Operational Activity Banks (BBKU) revealed the high degree ofviolation in the standard of fieldwork. In the International level, is the breakout of the cases of Enron-Arthur Anderson, World Com-Adhur Anderson, Xerox and Merck, which showed the violation of auditor's independence.This paper will try to describe how performance of Public Accounting Firms which are member of Capital Market's Accountant Forum in Indonesia. These perfor-mance will be evaluated in Auditing Standards and Quality Conticl Implementation.Keywords: Financial report, auditing standard, quality control, public accounting firm's